ENVIRONMENTAL DISCLOSURE AND FIRM VALUE: THE MODERATING ROLE OF BOARD SIZE - Tutik Arniati; Muslichah Muslichah; Nunung Nurastuti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to examine the impact of environmental disclosure on firm value, with board size serving as a moderating variable. The study population comprises state-owned Enterprises (SOEs) listed on the Indonesian Stock Exchange from 2019 to 2023. A sample of 14 SOEs was acquired through purposeful sampling. The research findings indicate that environmental disclosure does not influence business value, and board size does not alter the link between these two factors. Despite the study's findings indicating that direct and moderating impacts are insignificant, this does not imply that environmental disclosure lacks importance. Organizations must enhance transparency and the execution of sustainability policies to generate enduring value. The government and regulators may contemplate more robust policies that connect environmental performance with economic incentives, so enhancing the market's appreciation of environmental disclosure and augmenting corporate value.